Examination of the mechanism of Piezo ion channel in 5-HT synthesis in the enterochromaffin cell and its association with gut motility - Zhu, Zhenya; Chen, Xiaolong; Chen, Shuang; Hu, Chenmin; Guo, Rui; Wu, Yuhao; Liu, Ziyu; Shu, Xiaoli; Jiang, Mizu (Frontiers in Endocrinology, 2023)
In the gastrointestinal tract, serotonin (5-hydroxytryptamine,5-HT) is an important monoamine that regulates intestinal dynamics. QGP-1 cells are human-derived enterochromaffin cells that secrete 5-HT and functionally express Piezo ion channels associated with cellular mechanosensation. They can be blocked by Grammostolaspatulata mechanotoxin 4 (GsMTx4), a spider venom peptide that inhibits cationic mechanosensitive channels. The primary aim of this study was to explore the effects of GsMTx4 on 5-HT secretion in QGP-1 cells in vitro. We investigated the transcript and protein levels of the Piezo1/2 ion channel, tryptophan hydroxylase 1 (TPH1), and mitogen-activated protein kinasesignaling pathways. In addition, we observed thatGsMTx4 affected mouse intestinal motility in vivo. Furthermore, GsMTx4 blocked the response of QGP-1 cells to ultrasound, a mechanical stimulus.The prolonged presence of GsMTx4 increased the 5-HT levels in the QGP-1 cell culture system, whereas Piezo1/2 expression decreased, and TPH1 expression increased. This effect was accompanied by the phosphorylation of the p38 protein. GsMTx4 increased the entire intestinal passage time of carmine without altering intestinal inflammation. Taken together, inhibition of Piezo1/2 can mediate an increase in 5-HT, which is associated with TPH1, a key enzyme for 5-HT synthesis. It is also accompanied by the activation of the p38 signaling pathway. Inhibitors of Piezo1/2 can modulate 5-HT secretion and influence intestinal motility.